Penerapan Model Pembelajaran Problem Based Learning (PBL) untuk Meningkatkan Hasil Belajar IPA - Anita, Wa; Lessy, Djaffar (LP2M IAIN Ambon, 2024)
This research is motivated by the monotony of the teacher's use of the lecture method in learning which has an impact on low student learning outcomes. The purpose of this study was to determine the increase in student learning outcomes through the application of problem-based learning models in science subjects. This research is a class action research. The subjects of this study were 25 class VIII students of SMP Negeri 23 Ambon. The results showed that the learning outcomes of students in the material of the human excretory system after the problem based learning model was applied in cycle I there were 10 students (40%) who completed while those who did not complete were 15 people (60%), in cycle II there were 23 people (92%) who completed while those who did not complete were 2 people (8%). The results of this study indicate that the application of the problem based learning model can improve the learning outcomes of class VIII students in the subject of the human excretory system at SMP Negeri 23 Ambon.